Ablation treatment of primary and secondary liver tumors under contrast-enhanced ultrasound guidance in field practice of interventional ultrasound centers. A multicenter study. Issue 105 (August 2018) - Francica, Giampiero; Meloni, Maria Franca; Riccardi, Laura; de Sio, Ilario; Terracciano, Fulvia; Caturelli, Eugenio; Iadevaia, Maddalena Diana; Amoruso, Annabianca; Roselli, Paola; Chiang, Jason; Scaglione, Mariano; Pompili, Maurizio
Highlights: Not all tumor nodules are clearly detectable in conventional B-mode US. Localization and targeting of small HCC nodules and metastases with inadeguate ultrasound may decrease ablation effectiveness. Contrast enhanced ultrasound can be used to guide percutanepus ablation in the case of undetectable or poorly visible targets. This study represents a snapshot of the use of CEUS-guided ablation in real practice of Interventional Ultrasound Centers. Abstract: The present retrospective study was aimed at characterizing the clinical impact of contrast-enhanced ultrasound (CEUS) as a guidance technique for ablation of primary and secondary liver tumors at six interventional ultrasound centers. 148 patients (103M/45F, median age 74 yrs.) with 151 liver target lesions (median size 15 mm, 86.7% Hepatocellular Carcinomas) in whom CEUS guidance was used for Percutaneous Ethanol Injection (35.2%), Radiofrequency (46.3%) and Microwave (18.5%) were selected during the period 2008–2016. CEUS-guided ablations represented 7.3% (range 2.5%–13.8%) of 2015 ablative sessions performed at the participating centers. Indications to CEUS-guided ablation were: improvement of conspicuity of the target (28.5%), a target lesion undetectable on B-mode ultrasound (29.8%), detection of viable areas in nodules with either incomplete ablation or local tumor progression (41.7%). Overall, complete radiological ablation was obtained in 113/151 tumors (74.8%), with heat-based techniques (RF and MW) achieving higher rate of successful ablation (86.7%) than PEI (51%). Neither deaths nor major complications occurred after ablations. CEUS guidance demonstrates improved visibility and effectiveness in aiding ablation procedures that are otherwise technically difficult using only B-Mode US guidance.